Experimental Study on Size Effect and Fracture Properties of Polypropylene Fiber Reinforced Lightweight Aggregate Concrete - Hosseini Mehrab, Alireza; Esfahani, M. Reza (Periodica Polytechnica Civil Engineering, 2022)
In this experimental research, the effects of polypropylene fibers on size effect and fracture properties of lightweight aggregate concrete were studied. Two methods, including size effect method and work of fracture method, were used to investigate and analyze the size effect and fracture properties on different sizes of notched beams. The polypropylene fiber contents were 0.5%, 0.75%, and 1% by volume fraction. The obtained results revealed that increasing the polypropylene fibers in lightweight aggregate concrete relatively decreased the dependence of strength on the size effect parameter, while the addition of polypropylene fibers exhibited significant influence on decreasing the size dependency of ductility and fracture energy in lightweight aggregate concrete. Moreover, the increase of polypropylene fibers improved the total fracture energy (GF), initial fracture energy (Gf), characteristic length (lch), length of fracture process zone (cf), and critical stress intensity factor (KIc) of lightweight aggregate concrete in both size effect method and work of fracture method. This increase was more significant in work of fracture method because of considering the post-peak behavior. The size effect method was suitable and accurate for plain lightweight aggregate concrete. The GF ⁄ Gf ratio increased from 2.88 in plain lightweight aggregate concrete to 12.26 in polypropylene fiber reinforced lightweight aggregate concrete.